2022
DOI: 10.4103/abhs.abhs_26_22
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition knowledge of caregivers working in health and education centers for children with special healthcare needs

Abstract: Background: Children with special healthcare needs are recognized as a high-risk group for malnutrition. Caregivers have a strong influence on the dietary habits of their students, therefore, adequate nutrition knowledge among caregivers and educators has a great potential in improving the health of children. The purpose of this study is to assess the level of nutrition knowledge and demographic influences of knowledge among caregivers working in health and education centers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…In Bangladesh, a study done by Hossain et al ( 2019 ) reported that the majority of caregivers had a low perception of the importance of eating a variety of foods. However, this was in contrast to an Arabian study done by Ismail et al ( 2022 ), which reported that caregivers were knowledgeable about the importance of consuming fruits and vegetables daily, which is good for health. However, this knowledge may not necessarily translate to positive behaviour of offering children a variety of foods that would provide vitamins and minerals.…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…In Bangladesh, a study done by Hossain et al ( 2019 ) reported that the majority of caregivers had a low perception of the importance of eating a variety of foods. However, this was in contrast to an Arabian study done by Ismail et al ( 2022 ), which reported that caregivers were knowledgeable about the importance of consuming fruits and vegetables daily, which is good for health. However, this knowledge may not necessarily translate to positive behaviour of offering children a variety of foods that would provide vitamins and minerals.…”
Section: Discussioncontrasting
confidence: 87%
“…Similarly, in China, according to the study done by Shao et al ( 2022 ), caregivers were aware that poor diets can lead to overweight and obesity, while in Bangladesh, a study done by Rahman et al ( 2016 ) reported that caregivers perceived that healthy foods do not taste as good as unhealthy foods. The Arabian study done by Ismail et al ( 2022 ) reported that caregivers indicated that foods that are low in fibre can cause health issues and can lead to diseases. An Ethiopian study done by Gebru et al ( 2022 ) and a Nepal study done by Sharma et al ( 2018 ) reported that caregivers perceived that healthy eating has benefits of contributing to good health and improved long-term consequences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The senior caregivers have possibly had 3–10 more rounds of pre-school child-care experience than the junior ones. It’s argued that accumulated experiences increase particular knowledge [ 40 ]. Accordingly, older caregivers are wont to possess greater knowledge than their juniors due to their longer participation in, for example, the national twice-yearly VAS programme, interaction with the healthcare system/professionals and peers, and self-discovery through the child-feeding chores.…”
Section: Discussionmentioning
confidence: 99%